ORGANIZATION OF RADIATION AND CHEMICAL PROTECTION AND PROCEDURE FOR IMPLEMENTATION OF PROTECTIVE MEASURES UNDER COMBAT CONDITIONS - Yulia Yuryevna Myasnikova; Ergashev Shuhrat Sobirjonovich (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract The article reveals the applied aspects of the functioning of the radiation and chemical protection system (RHZ) in modern combat conditions. The work analyzes the sequence of actions of the medical service and personnel when exposed to the factors  of  weapons  of  mass  destruction.  Methods  of  conducting  exploration,  the procedure for switching to protective equipment and the organization of degassing and decontamination measures are considered. Particular attention is paid to maintaining the functionality of units through timely indication of threats and the use of personnel protective equipment.